Prevalência dos marcadores da infecção pelo vírus da hepatite B em candidatos a primodoadores de sangue em Jataí, sudoeste goiano - ANJOS, Giulena Rosa Leite Cardoso dos (2009)
To estimate the prevalence and evaluate risk factors to hepatitis B virus infection among candidates to first-time blood donnors in Jataí, southwest region of Goiás, 984 individulas were interviewed, blood samples were collected and screened for HBV markers (HBsAg, anti-HBs and anti-HBc) by enzyme immunoassay (ELISA). Most subjects were male (55.6%), from Jataí city (74.4%), aged < 40 years (71.5%) and had secundary education (77.2%). Almost half of them reported family income over US$500.00. An overall HBV prevalence of 6.9% (95% CI: 5.4 to 8.7) was found: 68 (6.9%) were anti-HBc-positive, three (0.3%) HBsAg-positive, and 41 (4.2%) anti-HBs-positive. Being from Jataí city (OR: 2.3, 95% CI: 1.0 to 5.0), having a history of blood transfusion (OR: 2.4, 95% CI: 1.2 to 4.9), having a piercing/tatooing (OR: 2.0, 95% CI: 1.2 to 3.6), having a history of drug use (OR: 2.6; CI 95%: 1.2-5.5), having unsafe sex (OR: 2.0; CI 95%: 1.1-3.6), having a sexual partner with hepatitis (OR: 16.5, 95% CI: 3.1 to 86.4), history of STD (OR 2.9, CI 95%: 1.4-5.8), and prostitution (OR: 2.4, 95% CI: 1.02-5.4) were factors independently associated with HBV positivity. It was found that the clinical screening had a sensitivity of 69%, specificity of 60.8%, positive predictive value of 11.6% and negative predictive value of 96.4%, respectively. The findings of this study suggest a low prevalence of hepatitis B in the southwest of Goias. However, the stricter association of HBV infection to risk factors/behaviors highlights the need for intensification of prevention programs for hepatitis B and other STDs in our region.